1988
DOI: 10.1161/01.str.19.6.669
|View full text |Cite
|
Sign up to set email alerts
|

Predicting survival after stroke: a three-year follow-up.

Abstract: We examined characteristics associated with a high risk of mortality within 3 years after a stroke. Analyses are based on data from a population-based register of stroke events that occurred in Auckland (total population 829,545), New Zealand during a 1-year period in 1981-1982 and a 3-year follow-up study of all survivors (97% complete). Statistical techniques that allow for the simultaneous evaluation of multiple factors indicated that retention of consciousness, decreasing age, and place of residence at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
41
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 22 publications
(9 reference statements)
13
41
1
Order By: Relevance
“…40,43 One of the key findings of our study was that, out of the factors such as male sex, past history of TIA, abnormal respiratory pattern, abnormal pupillary size and reaction, abnormal serum urea level, hemorrhagic stroke, aspiration pneumonitis, and worsening GCS that were found to be significantly related to mortality only aspiration pneumonitis and worsening GCS independently predicted stroke mortality for diabetic patients with stroke. This finding, which was consistent with reports from studies conducted on stroke from all causes, 42,45 has significant implication for treatment as, in resource poor setting, identification of predictors of death is of paramount importance for clinicians, so that specific therapies and management strategies can be applied to patients at high risk of dying.…”
supporting
confidence: 88%
“…40,43 One of the key findings of our study was that, out of the factors such as male sex, past history of TIA, abnormal respiratory pattern, abnormal pupillary size and reaction, abnormal serum urea level, hemorrhagic stroke, aspiration pneumonitis, and worsening GCS that were found to be significantly related to mortality only aspiration pneumonitis and worsening GCS independently predicted stroke mortality for diabetic patients with stroke. This finding, which was consistent with reports from studies conducted on stroke from all causes, 42,45 has significant implication for treatment as, in resource poor setting, identification of predictors of death is of paramount importance for clinicians, so that specific therapies and management strategies can be applied to patients at high risk of dying.…”
supporting
confidence: 88%
“…, and other available in studies, 21 we were able to ill of our cases into one of subtypes of stroke. Some previous studies used a clinical scoring system that appears more accurate than an unstructured clinical ADL indicates activities of daily living.…”
mentioning
confidence: 71%
“…The trend of increasing case-fatality rate with increasing age was only present in those who were independent before stroke. In another study Bonita et al 21 used residence as a surrogate measure of disability and found that those patients who lived in institutions at the time of a stroke had a very poor prognosis independent of a number of other variables.…”
mentioning
confidence: 99%
“…Woo et al 12 administered a mental status screen 3 months after stroke onset to 216 subjects and found that factors predicting mortality after 20 months included older age, history of ischemic heart disease, a low mental status test score, low serum cholesterol, low Glasgow Coma Scale score on admission, and left ventricular hypertrophy. In another study, 10 institutional care before stroke onset, whether an indicator of physical or cognitive disability or both, was an independent predictor of late mortality.…”
Section: Discussionmentioning
confidence: 92%